Gaze‐evoked nystagmus induced by alcohol intoxication. (17th January 2017) - Romano, Fausto; Tarnutzer, Alexander A.; Straumann, Dominik; Ramat, Stefano; Bertolini, Giovanni
Abstract : Key points: The cerebellum is the core structure controlling gaze stability. Chronic cerebellar diseases and acute alcohol intoxication affect cerebellar function, inducing, among others, gaze instability as gaze‐evoked nystagmus. Gaze‐evoked nystagmus is characterized by increased centripetal eye‐drift. It is used as an important diagnostic sign for patients with cerebellar degeneration and to assess the 'driving while intoxicated' condition. We quantified the effect of alcohol on gaze‐holding using an approach allowing, for the first time, the comparison of deficits induced by alcohol intoxication and cerebellar degeneration. Our results showed that alcohol intoxication induces a two‐fold increase of centripetal eye‐drift. We establish analysis techniques for using controlled alcohol intake as a model to support the study of cerebellar deficits. The observed similarity between the effect of alcohol and the clinical signs observed in cerebellar patients suggests a possible pathomechanism for gaze‐holding deficits. Abstract: Gaze‐evoked nystagmus (GEN) is an ocular‐motor finding commonly observed in cerebellar disease, characterized by increased centripetal eye‐drift with centrifugal correcting saccades at eccentric gaze. With cerebellar degeneration being a rare and clinically heterogeneous disease, data from patients are limited. We hypothesized that a transient inhibition of cerebellar function by defined amounts of alcohol may provide a suitable model to study gaze‐holding deficits in cerebellar disease. We recorded gaze‐holding at varying horizontal eye positions in 15 healthy participants before and 30 min after alcohol intake required to reach 0.6‰ blood alcohol content (BAC). Changes in ocular‐motor behaviour were quantified measuring eye‐drift velocity as a continuous function of gaze eccentricity over a large range (±40 deg) of horizontal gaze angles and characterized using a two‐parameter tangent model. The effect of alcohol on gaze stability was assessed analysing: (1) overall effects on the gaze‐holding system, (2) specific effects on each eye and (3) differences between gaze angles in the temporal and nasal hemifields. For all subjects, alcohol consumption induced gaze instability, causing a two‐fold increase [2.21 (0.55), median (median absolute deviation); P = 0.002] of eye‐drift velocity at all eccentricities. Results were confirmed analysing each eye and hemifield independently. The alcohol‐induced transient global deficit in gaze‐holding matched the pattern previously described in patients with late‐onset cerebellar degeneration. Controlled intake of alcohol seems a suitable disease model to study cerebellar GEN. With alcohol resulting in global cerebellar hypofunction, we hypothesize that patients matching the gaze‐holding behaviour observed here suffered from diffuse deficits in the gaze‐holding system as well. Key points: The cerebellum is the core structure controlling gaze stability. Chronic cerebellar diseases and acute alcohol intoxication affect cerebellar function, inducing, among others, gaze instability as gaze‐evoked nystagmus. Gaze‐evoked nystagmus is characterized by increased centripetal eye‐drift. It is used as an important diagnostic sign for patients with cerebellar degeneration and to assess the 'driving while intoxicated' condition. We quantified the effect of alcohol on gaze‐holding using an approach allowing, for the first time, the comparison of deficits induced by alcohol intoxication and cerebellar degeneration. Our results showed that alcohol intoxication induces a two‐fold increase of centripetal eye‐drift. We establish analysis techniques for using controlled alcohol intake as a model to support the study of cerebellar deficits. The observed similarity between the effect of alcohol and the clinical signs observed in cerebellar patients suggests a possible pathomechanism for gaze‐holding deficits.